Remaking Contested Architectural Heritage, Rethinking Public Space - Otero-Pailos, Jorge; Fernández-Morales, Angélica; Sebastian Franco, Sergio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
The management of contested heritage, understood as that associated with ethically questionable historical episodes, or episodes subject to controversy in today's society, should include that of buildings and public spaces. Those can be heritage sites but also spaces that currently house those monuments, or public spaces in which social movements derived from historical episodes take place. This issue of Zarch presents essays that examine new ways of remaking said contested heritage, and approach this question through the conceptual framework of experimental preservation, and that conceive of heritage as a creative and dynamic third realm of real and imaginary, physical and emotional, technological and social interactions between objects and subjects involved in processes of future-making.
Keywords: Experimental preservation; Public space; Monuments; Contested heritage